2021
DOI: 10.1039/d1re00216c
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of furfural electrochemical hydrogenation and hydrogenolysis in acidic media on copper

Abstract: Electrochemical processes can be implemented for the valorization of biomass-derived species such as furfural to generate fine chemicals and fuels. The electrochemical hydrogenation and hydrogenolysis (ECH) of furfural (FF) can...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
57
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(59 citation statements)
references
References 34 publications
1
57
1
Order By: Relevance
“…Our results show that a decrease in pH promotes hydrogenolysis [i.e., the faradaic efficiency (FE) for DMF production increases from 1 to 28 % when the pH is lowered from 9 to 2] while suppressing hydrogenation. A similar trend has been observed for the reduction of furfural; [21][22][23] however, the reason for the observed pH dependence has not yet been elucidated in any of the prior studies. In this study, we computationally examined all possible HMF reduction pathways and the most feasible mechanistic routes [i.e., hydrogen atom transfer (HAT) and proton coupled electron transfer (PCET)] to form the intermediates for each of the pathways.…”
Section: Introductionsupporting
confidence: 69%
See 2 more Smart Citations
“…Our results show that a decrease in pH promotes hydrogenolysis [i.e., the faradaic efficiency (FE) for DMF production increases from 1 to 28 % when the pH is lowered from 9 to 2] while suppressing hydrogenation. A similar trend has been observed for the reduction of furfural; [21][22][23] however, the reason for the observed pH dependence has not yet been elucidated in any of the prior studies. In this study, we computationally examined all possible HMF reduction pathways and the most feasible mechanistic routes [i.e., hydrogen atom transfer (HAT) and proton coupled electron transfer (PCET)] to form the intermediates for each of the pathways.…”
Section: Introductionsupporting
confidence: 69%
“…We note that a few studies have previously investigated electrochemical hydrogenation and hydrogenolysis mechanisms of simpler aldehydes like furfural and benzaldehyde [21,23,38,39] . However, no studies suggested the possibility that the hydrogenation and hydrogenolysis intermediates may require different hydrogenation (HAT vs. PCET) mechanisms.…”
Section: Resultsmentioning
confidence: 92%
See 1 more Smart Citation
“…Kinetic analysis of their reactions suggests that an Eley–Rideal-type mechanism is most likely operative in their system, which means the addition of hydrogen occurs by PCET. On the other hand, Biddinger and co-workers investigated the hydrogenation (production of furfuryl alcohol) and hydrogenolysis (production of methyl furan) of furfural in acidic media on Cu . The noncompetitive Langmuir–Hinshelwood mechanism was found to best fit their experimental data for both reactions, which means that the addition of H-atoms is achieved by HAT.…”
Section: Electrochemical Reductive Valorization Via Hydrogenation And...mentioning
confidence: 65%
“…Recently, we conducted an initial rate study for FF ECH over Cu in acidic media to better understand the electrochemical kinetics. 29 This initial rate study avoided reaching significant concentrations of FA and MF, thereby mitigating the impact of the concentration-dependent undesired reactions onto the desired electrochemical kinetics. We found the FF ECH over Cu in acidic media followed a noncompetitive Langmuir−Hinshelwood model for both FA and MF, where FA and MF were produced via two different intermediate species.…”
Section: Introductionmentioning
confidence: 99%